ERS International Congress, 2020: highlights from the Epidemiology and Environment Assembly - van der Plaat, DA; Rantala, AK; Alif, SM; Karadoğan, D; Cai, Y; Dumas, O (European Respiratory Society, 2021)
In this article, early career members of the Epidemiology and Environment Assembly of the European Respiratory Society (ERS) summarise a selection of five sessions from the Society's 2020 virtual congress. The topics covered include risk factors for chronic respiratory diseases over the life course, from early life origins to occupational exposures in adulthood, and the interplay between these risk factors, including gene-environment interactions. Novel results were also presented on smoking prevention and potential risks of vaping. Finally, the challenges and opportunities for epidemiological and environmental research brought by the coronavirus disease-2019 (COVID-19) pandemic were a major topic of this year's congress.